THE IMPLEMENTATION OF GOOGLE SHEET-BASED FINANCIAL REPORTS AT PT SINAR MAKMUR TERANG SEJATI - Isnaini Nuzula Agustin; Jeffry Setiawan Hartono (Universitas Internasional Batam, 2022)
PT Sinar Makmur Terang Sejati is a business engaged in finance, namely foreign exchange (forex) which consists of various currencies such as SGD, MYR, USD, and others. PT Sinar Makmur Terang Sejati is located in Komp. Bumi Indah Blok B no 5 and has been established since 2017. The company's financial records have so far been done manually, which may lead to an inefficiency and error proneness. This project aims to solve the problems faced by PT Sinar Makmur Terang Sejati.The method used in this community service activity is scrutinizing qualitative information through interviews and observations. Next, an output design is carried out based on the transaction book. The main output of this activity is a Google Sheet-based financial report that shows a statement of financial position, ending balance and income statement.This community service activity is divided into three main stages, namely preparation (output design), implementation and evaluation (output use) and reporting stage. The implementation of recording financial transactions using Google Sheets in knowing the financial position, ending balance and profit and loss is proven to be able to speed up and simplify the decision-making process for the business run by PT Sinar Makmur. This is also very helpful for management in knowing what foreign exchange balances they have and being able to make transactions as quickly as possible.